ANALISIS KESADARAN DIRI REMAJA TERHADAP NORMA SOSIAL SEBAGAI UPAYA PENCEGAHAN PERNIKAHAN DINI AKIBAT KEHAMILAN DI LUAR NIKAH (STUDI KASUS DI DESA MUARA DELANG, KEC. TABIR SELATAN, KAB. MERANGIN) - Nurbaeti, Shevi; Ichsan, Muhammad; Wela Sasih, Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the high rate of early marriage in Muara Delang Village, which ranks second among eight villages in Tabir Selatan District. Based on data from the Marriage Management System (Simkah) website, 57 teenagers have married early in the past three years. This study aims to determine adolescents' self-awareness of social norms as a form of prevention against early marriage due to premarital pregnancy, as well as efforts to foster self-awareness. Data were obtained through observation, interviews, and documentation. The results of this study indicate that adolescents' self-awareness of social norms in Muara Delang Village has been understood, but has not been consistently applied in daily life. Meanwhile, efforts to foster adolescent self-awareness are carried out through various efforts, including strengthening the role of the family, instilling moral and religious values, reproductive health education, providing positive activities, cross-sectoral collaboration, and education on wise media use.